2022
DOI: 10.3390/jpm12030409
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR4 Rs4986791 Polymorphism and TLR9 Haplotypes with Acute Myeloid Leukemia Susceptibility: A Case-Control Study of Adult Patients

Abstract: Toll-like receptors (TLRs) have an important role in innate immunity, and single nucleotide polymorphisms (SNPs) of TLR genes influence the risk of developing hematological malignancies. We aimed to evaluate the effect of TLR2 (rs5743708), TLR4 (rs11536889, rs4986790, rs4986791), TLR9 (rs187084, rs352140, rs5743836) on AML risk, the relation between investigated SNPs and somatic mutations, clinical features, and the overall survival of adult AML patients. All mentioned SNPs were genotyped in 511 AML cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…There were 6 and 11 studies involving colorectal and GCs, separately. Others include acute myeloid leukemia, [ 73 ] bladder cancer, [ 68 ] breast cancer, [ 61 ] cervical cancer, [ 65 ] endometrial cancer, [ 66 ] malignant melanoma, [ 67 ] lung cancer, [ 62 ] liver cancer, [ 71 ] and chronic myeloproliferative neoplasm [ 72 ] also included in our meta-analysis. However, each of them has less than two research articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 6 and 11 studies involving colorectal and GCs, separately. Others include acute myeloid leukemia, [ 73 ] bladder cancer, [ 68 ] breast cancer, [ 61 ] cervical cancer, [ 65 ] endometrial cancer, [ 66 ] malignant melanoma, [ 67 ] lung cancer, [ 62 ] liver cancer, [ 71 ] and chronic myeloproliferative neoplasm [ 72 ] also included in our meta-analysis. However, each of them has less than two research articles.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of tumors are involved, which encompass PC, [38][39][40][41][42][43][44] GC, [27,[45][46][47][48][49][50][51][52][53] colorectal cancer, [28,29,[54][55][56][57] non-Hodgkin's lymphoma, [58][59][60] breast cancer, [61] lung cancer, [62] and other tumors. [46,[63][64][65][66][67][68][69][70][71][72][73] The ethnic distribution of subjects is mainly Caucasian(n = 31) and Asian(n = 5). Some studies did not make a precise distinction between the ethnic groups, and we defined these as mixed ethnic groups (n = 2).…”
Section: Features Of the Included Studiesmentioning
confidence: 99%
“…TLRs detect conserved molecules that are specific to individual microbial species, termed PAMPs, as well as endogenous molecules known as DAMPs. Activation of TLRs may trigger immune responses and inflammatory processes [28,29]. TLR4 is one the most important and well-characterized TLRs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, autoantibody production and induction of inflammatory cells are modulated through the TLR9 signaling pathway [ 14 16 ]. Previous studies have revealed the importance of TLR9 gene variants in the pathogenesis of autoimmune diseases such as Systemic lupus erythematosus (SLE) [ 17 – 19 ], rheumatoid arthritis (RA) [ 20 ], ankylosing spondylitis (AS) [ 21 ], acute myeloid leukemia (AML) [ 22 ], Hashimoto’s autoimmune thyroiditis [ 23 ], and Graves’ disease (GD) [ 24 ]. However, their possible association with BD has provided controversial results [ 24 ].…”
Section: Introductionmentioning
confidence: 99%